Limiting Cash Circulation as a Means to Combat Shadow Economy - G. S. Panova; E. N. Valetdinova (Vestnik MGIMO-Universiteta)
The article deals with actual problems of modern state and development prospects of cash circulation in Russia and abroad; the comparative analysis of monetization of the economy of Russia and foreign countries; quantitative parameters of aggregate money turnover, including the value of cash and non-cash spheres; the correlations of macroeconomic variables and indicators of cash circulation in Russia. Special attention is given by the authors to the limitations of cash payments and settlements in the fight against shadow economy. In particular, researched the level of shadow economy; the relationship between cash money circulation and shadow economy; the problems encountered by foreign states in imposing administrative limits on the amount of payments in cash; provides specific recommendations and outlines the required steps to introduce such restrictions in Russia. It is concluded that the limitation of the maximum size of payments in cash can lead to simultaneous reduce the underground economy because revenues derived from the hidden and informal economic activities can be translated in non-cash form. However, in the long run, when adopting legislative restrictions on the payment of funds by individuals on their own bank accounts or, for example, need to prove the lawful origin of money if you make them into a bank account to limit payments in cash will be the first step towards the goal of reducing shadow economy in Russia. In general, limiting the cash circulation - multi-factor task - that requires the solution of economic, political, social, administrative, psychological problems. The overall decrease in cash money (up to the optimum, economically justified level), it will lead to lower inflation rates, the level of corruption, will improve the investment climate and the liberalization of the credit market in our country.